Favela associations: Between repression, violence and politics - Saaristo, S. (Suomen Antropologi, 2016)
The article analyzes the dynamics and structures of oppression and marginalization of favela residents in Rio de Janeiro, Brazil, as well as the modalities of agency that members of favela residents’ associations have used to respond to the changing situation. I analyze the spatial differentiation between favelas and the formal parts of the city, and how this is reflected in the notion of how the favelas and their residents are characterized. Some single elements, such as violence, have been taken as markers to define the whole space of the favelas as well as their residents. In state policies, the views as well as the agency of favela residents have often been ignored, thereby treating the favela residents as only subjects of different politics and measures. The study presents the analysis the members of favela associations make of state politics, and how their own modalities of agency have contributed both to maintaining the structures of oppression as well as challenging it. The focus is on the favela residents’ associations in two favelas of Southern Rio